Battling malaria in rural Zambia with modern technology: a qualitative study on the value of cell phones, geographical information systems, asymptomatic carriers and rapid diagnostic tests to identify, treat and control malaria - David Nygren; Arvid Lissel Isaksson (AOSIS, 2014)
During the last decade much progress has been made in reducing malaria transmission in Macha, Southern Province, Zambia. Introduction of artemisinin combination therapies as well as mass screenings of asymptomatic carriers is believed to have contributed the most. When an endemic malaria situation is moving towards a non-endemic situation the resident population loses acquired immunity and therefore active case detection and efficient surveillance is crucial to prevent epidemic outbreaks. Our purpose was to evaluate the impact of cell phone surveillance and geographical information systems on malaria control in Macha. Furthermore, it evaluates what screening and treatment of asymptomatic carriers and implementation of rapid diagnostic tests in rural health care has led to. Ten in-depth semistructured interviews, field observations and data collection were performed at the Macha Research Trust and at surrounding rural health centers. This qualitative method was inspired by rapid assessment procedure. The cell phone surveillance has been easily integrated in health care, and its integration with Geographical Information Systems has provided the ability to follow malaria transmission on a weekly basis. In addition, active case detection of asymptomatic carriers has been fruitful, which is reflected in it soon being applied nationwide. Furthermore, rapid diagnostic tests have provided rural health centers with reliable malaria diagnostics, thereby decreasing excessive malaria treatments and selection for drug resistance. This report reflects the importance of asymptomatic carriers in targeting malaria elimination, as well as development of effective surveillance systems when transmission decreases. Such an approach would be cost-efficient in the long run through positive effects in reduced child mortality and relief in health care.